The Risk and Strategies of Potato Production in Garut, Indonesia - Karissa Nurbudiati; Eliana Wulandari (Universitas Sebelas Maret, 2020)
The fluctuation of potato production has been caused by production risk in on-farm sector. This research aims to identify the sources of production risk in potato production and analyze the strategies to overcome the production risk. This research was conducted at Cantigi Farmers’ Group, which has been actively producing potato in Cikajang Sub-district, Garut Regency, West Java. The data were collected from all 35 members of the Cantigi Farmers’ Group. This study used Z-Score and Value at Risk analyses. The results showed that the sources of potato production risk that occurred in the Cantigi Farmers’ Group were pests, diseases, rainfall, seed quality, managerial ability and soil fertility. Mitigation strategies can be used to overcome the risk sources such as by using intercropping method, plant-based pesticides, natural enemies, proper water management and drainage. Preventive strategies can be used to overcome the risk sources such as by using plant-based pesticides, organic fertilizers, assistance from local extension agents, in collaboration with certified seed breeders in the surrounding area and attending the training of how to breed properly. The research on potato production risk in Cikajang Sub-district is very significant considering that, to the best of authors’ knowledge, the analysis of potato production risks has not been conducted yet in this important area of potato producing. This study was conducted in a limited scope of variable, therefore, a further research of potato production risks is suggested to be performed in a wider variable scope.